Literasi Keuangan dan Keputusan untuk Berkonsultasi dengan Profesional - Shresta Purnamasari (JEMAP, 2020)
Previous literatures showed that financial literacy was a determining factor for an individual's decision to consult with professionals. However, the relationship between the two may be simultaneous, so the estimation method of causality testing has been imprecise. The respondents from this study were 115 students of Masters of Management degree of Gadjah Mada University, specific on Executive Class in Jakarta. This study found that there was a simultaneous relationship between financial literacy and consultation decisions. Furthermore, causality testing was carried out using the Control Function estimation method, which contained instrumental variables in the form of family economic shocks that had been experienced in the last twenty years. This estimation method was useful to avoid endogeneity problems. The finding of this study was instrumented financial literacy significantly increased the probability of individuals to consult with professionals. Apart from the real benefits of consulting with professionals or level of professionality, a personal financial education model can be an alternative financial education that can be done by stakeholders.